2014
DOI: 10.1038/ncomms4892
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally selective chiral silicon metasurfaces based on infrared Fano resonances

Abstract: Metamaterials and metasurfaces represent a remarkably versatile platform for light manipulation, biological and chemical sensing, and nonlinear optics. Many of these applications rely on the resonant nature of metamaterials, which is the basis for extreme spectrally selective concentration of optical energy in the near field. In addition, metamaterial-based optical devices lend themselves to considerable miniaturization because of their subwavelength features. This additional advantage sets metamaterials apart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
366
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 439 publications
(375 citation statements)
references
References 73 publications
2
366
1
Order By: Relevance
“…supported on a lower-index substrate. [5][6][7][8][9][10][11][12][13] The metamaterial employed in the present study shows, however, that strong localized resonances can also be excited in "negative" dielectric nanostructures, i.e., a pattern formed by slots cut into a continuous layer of highindex material. The free-standing configuration has the additional advantage of maximizing refractive index contrast with the near-field environment and thereby resonance quality factor.…”
Section: Nano-optomechanical Nonlinear Dielectric Metamaterialsmentioning
confidence: 86%
See 2 more Smart Citations
“…supported on a lower-index substrate. [5][6][7][8][9][10][11][12][13] The metamaterial employed in the present study shows, however, that strong localized resonances can also be excited in "negative" dielectric nanostructures, i.e., a pattern formed by slots cut into a continuous layer of highindex material. The free-standing configuration has the additional advantage of maximizing refractive index contrast with the near-field environment and thereby resonance quality factor.…”
Section: Nano-optomechanical Nonlinear Dielectric Metamaterialsmentioning
confidence: 86%
“…In "all-dielectric" metamaterials nonradiative losses are a priori limited, so with appropriate design they can present even stronger optical resonances, and thereby generate stronger optical forces, than plasmonic counterparts. 22 Previous works have demonstrated that highindex media such as silicon can support optical frequency resonances [5][6][7][8][9][10][11][12][13] and we harness that characteristic here to engineer an ultrathin medium with optical properties that are highly sensitive to structural reconfiguration.…”
Section: Nano-optomechanical Nonlinear Dielectric Metamaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] It has been shown that plasmonic nanostructures forming 1D [7] elements, 2D metasurfaces, [8][9][10] and 3D metamaterials [11] can exhibit linear chiral response due to their own, intrinsic chirality. Also semiconductor nanostructures can exhibit chiral features.…”
mentioning
confidence: 99%
“…Importantly, the interference of electric and magnetic Mie-type resonant modes of the same strength allows for fundamentally new effects to be realized, such as unidirectional scattering 10 and unity transmission in the Huygens regime [11][12][13] . Furthermore, the Fano interference of bright and dark modes in the dielectric resonators [14][15][16] provides a pathway to obtaining narrowband resonances with quality-factors of up to several hundred 17 . Such quality factors open up new applications for dielectric metasurfaces, such as high-sensitivity sensors 14,15 and narrow-band filters 18 .…”
mentioning
confidence: 99%